The Role of Social Capital in Contributing to Lifestyle Brand-Related Content on Social Media - Ciunova-shuleska, Anita; Palamidovska sterjadovska, Nikolina; Bogoevska-gavrilova, Irena (Ss. Cyril and Methodius University in Skopje, Faculty of Economics-Skopje, 2022)
The purpose of this research is to analyze the differences in users’ intentions to like, share, and comment on lifestyle brand-related content on social media based on the social capital focus. In this paper, social capital is conceptualized as a positive outcome of users’ interaction on social media, focusing on bonding and bridging dimensions of social capital. However, to examine the differences in intentions to like, share, and comment between social media users with a bridging focus and with а bonding focus, social capital is analyzed as a cause of social media engagement in terms of liking, sharing, and commenting on brand-related content on social media. There was carried out a survey of social media users by using questionnaires. Factor analysis and a one-way ANOVA test were used on a data set of 415 effective responses. The respondents were divided into two groups based on their social capital focus. The results of factor analysis identified the factors as conceptualized in the literature. The results of the one-way ANOVA test indicated the existence of significant differences in intentions to like, share, and comment on lifestyle brand-related content depending on the social media users’ social capital focus. Social media users with a bridging focus showed stronger intentions to like, share, and comment on lifestyle brand-related content compared to social media users with a bonding focus. The findings of this research study may help social media marketing managers successfully design and implement effective lifestyle brand-related content depending on the users’ social capital focus.
Keywords: like, share, comment, lifestyle brand-related content, social capital